Optimizing Germination and Tillering of Sugarcane (Saccharum Officinarum L.) through Number of Eyed-Setts and Growth Regulators - De Leon, Richelle (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effects of growth regulators and eyed-sett number on the early growth performance of sugarcane under nursery conditions. It was anchored on the view that early sugarcane establishment is influenced by the interaction of biological characteristics of planting materials and agronomic interventions, particularly the application of plant growth regulators and variation in sett number. The study used an experimental approach employing a 2×4 factorial arrangement in a Completely Randomized Design with three replications. Treatments involved two levels of eyed-sett number and four growth regulator applications. Good-quality freshly harvested sugarcane setts were used as planting materials, and data were gathered through direct measurement of shoot length, root length, leaf area, and number of tillers at 45 days after planting. Soil analysis, proper crop management, and statistical treatment through the STAR Package Program and Tukey’s Honest Significant Difference Test supported the analysis of treatment effects. The findings showed that germination reached 98 percent across treatments, with generally vigorous plant stand and no observed pest or disease infestation. The number of eyed-setts alone did not significantly affect shoot length, root length, leaf area, or tiller production. In contrast, growth regulators had a more pronounced effect on early growth responses. Calcium chloride significantly improved root length and leaf area, while gibberellic acid produced the highest tiller count. The interaction between sett number and growth regulator was significant for root length and tiller production, with two-budded setts treated with Calcium chloride or Gibberellic acid showing the most favorable responses. The study concluded that growth regulator application is more critical than sett number alone in enhancing early sugarcane establishment under nursery conditions. It recommends the use of Calcium chloride or Gibberellic acid, particularly for two-budded setts, to improve the quality of sugarcane planting materials, while further studies are encouraged to determine the most effective treatment levels. The study aligns with SDG 8 by supporting agricultural productivity and livelihoods, as well as SDG 12 through improved planting material efficiency in crop production. It also relates to SDG 7 because sugarcane supports bioenergy-related production systems. In terms of sustainability impact, the study contributes to agricultural, socio-economic, and technological sustainability by promoting evidence-based nursery practices that can strengthen crop establishment, reduce inefficiencies, and support more sustainable sugarcane production systems.